2009
DOI: 10.1088/0953-4075/42/5/055003
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modelling of enhanced absorption Hanle effect resonances in85Rb

Abstract: We report on a detailed measurement of the enhanced absorption Hanle effect resonances in 85Rb. The effect was analysed with an experimental setup allowing for the control of each magnetic field component within 1 mG. The characterization deals with the dependence of resonances, observed under different magnetic field conditions, on the frequency, intensity and polarization of the exciting radiation field. An analytic model that precisely describes the resonance behaviour is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We derive algebraic expressions for the parameters of Hanle resonance line shapes in arbitrarily oriented magnetic fields that are valid (in the low-power limit) for arbitrary nL J ,F → n L J ,F electric dipole transitions. Although the GSHE with circularly polarized light has been studied by several groups in the past (see, e.g., [6,7,[19][20][21][22]), we are not aware of any publication that derives explicit expressions for the line shapes. In analogy to the classical (linear) HE, the linewidths of the GSHE resonances obey relations similar to Eq.…”
Section: Introductionmentioning
confidence: 99%
“…We derive algebraic expressions for the parameters of Hanle resonance line shapes in arbitrarily oriented magnetic fields that are valid (in the low-power limit) for arbitrary nL J ,F → n L J ,F electric dipole transitions. Although the GSHE with circularly polarized light has been studied by several groups in the past (see, e.g., [6,7,[19][20][21][22]), we are not aware of any publication that derives explicit expressions for the line shapes. In analogy to the classical (linear) HE, the linewidths of the GSHE resonances obey relations similar to Eq.…”
Section: Introductionmentioning
confidence: 99%
“…However, the latter approach is not well suited to extract characteristic system parameters, such as relaxation rate(s), by data fitting procedures. A third approach just uses empirical line shape functions to analyze the resonances [17], but gives little insight into the underlying mechanisms of the GSHE.…”
Section: A Scope Of the Present Workmentioning
confidence: 99%
“…The dark and bright resonances are the phenomena of EIT and electromagnetically induced absorption (EIA) [19][20][21], respectively. There have been many reports on CPT and EIT experiments in the Hanle configuration using alkali-metal atoms, such as 87 Rb, 85 Rb, K, and Cs in either a pure or buffer-gas-filled cell [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In the context of the effect of the external parameters on the CPT spectra, such as a stray magnetic field or the polarization of the laser beam, Nasyrov et al [28] reported a CPT experiment in the Hanle configuration for Cs atoms in a pure cell using an elliptically polarized beam and explained the results using a simple theoretical model.…”
Section: Introductionmentioning
confidence: 99%